Pemberdayaan Siswa dan Siswi Sekolah Menengah Pertama Islam Cepu Jawa Tengah Tentang Peningkatan Motivasi Belajar, Wawasan Berpikir dan Kewajiban Belajar ke Jenjang Perguruan Tinggi - Saragih, Muhammad Rizal; Rusdi, Rusdi; Hunein, Hamida; Sadewa, Prima; Hasan, Julian Muhammad (Jurnal PKM Manajemen Bisnis, 2024)
The aim of this community service is to increase learning motivation, insight into thinking and the obligation to study at the tertiary level for students and students at Cepu Islamic Middle School, Central Java. The method of community service is seminars and discussions. The population in this community service activity is 100 people, all of whom are students of Cepu Islamic Middle School, Central Java. The result of this community service is that all participants understand and apply all the material and discussions that occur during the event so that the goals of this service are achieved.